Pengaruh Dari Pematuhan Tata Tertib Sekolah dan Keikutsertaan Siswa Dalam Ekstrakurikuler Pramuka Terhadap Disiplin Siswa Dalam Belajar Pada Siswa SMA Swasta Akreditasi A di Kota Padang - Maya Sari; Agus Irianto (Jurnal Ecogen, 2020)
The purpose of this article was to study the effects of reversal of school rules and student participation in scout extracurricular activities on the learning discipline of high school accreditation A students in the city of Padang. This type of research was associative descriptive. The population in this study were 5340 respondents from Private an Accreditation Private Schools in Padang. The sampling technique was a two-stage cluster random sampling. The data used in this study are primary data and secondary data. The technique in collecting data was the form of a questionnaire. The instrument testing used a validity and reliability test. The data analysis techniques used descriptive analysis. Based on the results of this study it can be concluded that (1) there is an effect of student compliance with school rules with student learning discipline (2) there is no relation between student’s participation in scout on the learning discipline (3) Student participation in scout extracurricular influences compliance with school regulations.Keywords: obedience to school rules, scout extracurricular, learning discipline